(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the efficacy of doppler flow study in umbilical artery in the diagnosis and management of fetal growth retardation in small for gestational age fetuses detected by clinical examination. Study Design: Descriptive case series. Place and Duration of Study: This study was conducted at the Department of Obstetrics & Gynecology, Nishtar Hospital Multan from September 20, 2007 to June 19, 2008. Subjects and Methods: Subjects were selected from clinically diagnosed pregnant ladies visiting antenatal clinic or admitted in labour. Umbilical artery doppler flow study was done and perinatal outcome was assessed. On the basis of umbilical artery doppler flow study, the subjects were categorized into abnormal (group A) or normal (group B). Perinatal outcome of both these groups was compared on the basis of criteria mentioned in the proforma. Results: Out of 50 patients, 21 (42%) patients were having abnormal umbilical artery doppler flow study (Group A) and 29 (58%) patients were having normal umbilical artery doppler flow study (Group B). Emergency cesarean section, Preterm delivery, Low birth weight, admission of newborn to nursery, Low Apgar score (≤ 5) and Early neonatal death were significantly more in group A versus group B. Conclusion: There is a correlation between umbilical doppler velocimetry and an increased incidence of perinatal complications in intrauterine growth retarded fetuses.